FAKTOR PENYEBAB ALIH FUNGSI LAHAN PERTANIAN DI KAWASAN WISATA PUNCAK TETEMPANGAN (Studi Kasus: Desa Koha Kecamatan Mandolang Kabupaten Minahasa) - Veisy ., Sompie; Melsje Yellie Memah; Vicky R. B. Moniaga (Sam Ratulangi University, 2021)
This research aims to determine the factors causing the conversion of agricultural lands in Koha Village, Mandolang District, Minahasa Regency. This research was conducted from November 2019 to July 2020. The types of data used in this study were primary data and secondary data. Primary data was obtained from interviews with respondents using questionnaires while secondary data was obtained from previous research literature. The data analysis method in this research is descriptive analysis which is presented in tabular form. The method of determining the sample using the Purposive Sampling method. Respondents taken are land owners who convert agricultural land functions. The results showed that the conversion of agricultural land was influenced by 2 factors, namely (1) External Factors, where the high selling price of land was influenced by the strategic location of the land because the land was intended for tourist attractions so that the selling price was high. (2) Other internal factors, where some respondents use the proceeds from the sale for business capital and some respondents transfer the function of their agricultural land because there is no one to take care of it and the respondent's education level is influential in the negotiation process for selling agricultural land.